Inequity in Formal Health Care Use: Evidence from Rural Bangladesh1. (6th August 2014) - Hamid, Syed Abdul; Ahsan, Syed M.; Begum, Afroza; Asif, Chowdhury Abdullah Al
Abstract This paper analyses inequity in formal health care use in rural Bangladesh using data from a survey conducted of 4010 households drawn from 120 villages. We find that the use of formal health care is incredibly low (40 per cent); about two‐thirds of which is private health care, and only one‐fourth utilises public sector facilities. Inequity favours the better off, although the level of inequity is modest. Prevailing inequity resides mainly in the utilisation of private health care while non‐communicable diseases contribute significantly. Thus, the main public health concern in rural areas of Bangladesh is the low utilisation of formal health care (especially public health care), not inequity. Copyright © 2014 John Wiley & Sons, Ltd.